2019
DOI: 10.7717/peerj.7193
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of extracellular polymeric substances extracted from waste activated sludge as a renewable corrosion inhibitor

Abstract: Background Waste activated sludge (WAS) has recently gained attention as a feedstock for resource recovery. The aim of this study is to investigate the corrosion inhibition efficiencies of extracellular polymeric substances (EPS) extracted from WAS. Methods The studied corrosion inhibitors were tested with carbon steel in 3.64% NaCl saturated with CO2 at 25 °C, which is the typical oilfield environment. They were first prepared by EPS extraction (heating at 80 °C), followed by centrifugation for solid and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The corrosion inhibition capability of synthetic EPS was proven significant in this study. The trend in the IR spectrum of the synthetic EPS followed closely to the natural WAS EPS [8] as expected because it is formulated based on the chemical composition of natural WAS EPS. Similar to the natural WAS EPS, the FTIR results of synthetic EPS showed that functional groups O-H, N-H, C-N, C=O, and C-H were present.…”
Section: Ftirsupporting
confidence: 66%
See 3 more Smart Citations
“…The corrosion inhibition capability of synthetic EPS was proven significant in this study. The trend in the IR spectrum of the synthetic EPS followed closely to the natural WAS EPS [8] as expected because it is formulated based on the chemical composition of natural WAS EPS. Similar to the natural WAS EPS, the FTIR results of synthetic EPS showed that functional groups O-H, N-H, C-N, C=O, and C-H were present.…”
Section: Ftirsupporting
confidence: 66%
“…At 25°C, the maximum inhibition protection of synthetic EPS was 82% at a concentration of 153 mg/L. The previous study of WAS EPS inhibitor demonstrated an optimum inhibition performance of about 79% at a concentration of 1000 mg/L [8]. Even though the inhibition performance showed only a mere improvement of 3%, the inhibitor concentration was reduced by about 6.5 times.…”
Section: Effect Of Concentrationmentioning
confidence: 83%
See 2 more Smart Citations
“…It was also reported that natural products are used to either synthesize [37,104–105,107c,118b,119‐120,131a‐c,e,144] or modify other compounds [128c,f,131d] that have been tested as CIs in a CO 2 environment (Table S10 in Supplementary Material). In addition, the corrosion inhibition effectiveness of extracellular polymeric substances extracted from waste activated sludge [77] and berberine extracted from Coptis chinensis [67c] was evaluated for CS immersed in CO 2 ‐saturated 3.64 wt.% NaCl solution and for L360 steel immersed in CO 2 ‐saturated 3.5 wt.% NaCl solution, respectively. There were also studies on the corrosion inhibition role of gum arabic, [82] aqueous solutions of caffeine and nicotine, [94] and sophorolipids (a mixture produced by Starmerella bombicola with a carbon source of glucose and rapeseed oil) in CO 2 ‐saturated brine solutions (Table S11 in Supplementary Material).…”
Section: Corrosion Inhibition Of Steel In a Co2 Environmentmentioning
confidence: 99%